Local Economic Development Sebagai Upaya Terwujudnya Pembangunan Berkelanjutan - Meli Handayani Catur Putri; Novi Tri Putri (Convergence: The Journal of Economic Development, 2022)
The purpose of this paper is to describe the role of Local Economic Developmet (LED)  in achieving the Sustainable Development Goals (SDG;s). This paper uses previous research articles as a basis for describing the implementation of LED in various aspects and their relation to the achievemnet of the SDG’s. the results of the research show that LED is one way to achive the SDGs, especially with regard to inclusive and sustainable economic growth, full and produktive employment, and decent work for all.   Keywords: Local Economic Developmet1, Sustainable Development Goals2